UPAYA MENINGKATKAN KEMAMPUAN MENCERITAKAN KEMBALI SECARA TERTULIS TEKS IKLAN DENGAN MENERAPKAN METODE DISCOVERY LEARNING SISWA KELAS VIII C SEKOLAH MENENGAH PERTAMA NEGERI 6 TABANAN TAHUN PELAJARAN 2022 / 2023 - Suparta, I Made; Casvarina, Citra Dian (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2023)
The retelling of advertising text should be taught in grade VIII. However, based on initial research, not all students were able to retell advertising text. The class average score achieved was only 65.00%. This happens because students feel bored and the learning atmosphere is less supportive. The purpose of this study is to contribute thoughts/opinions in order to improve the ability to retell in writing the advertising text of students in grade VIIIth C of Sekolah Junior High School of Negeri 6 Tabanan in the 2022/2023 academic year. Thus, to improve students' ability to retell in writing the advertising text, the discovery learning method was applied. The results showed that the ability to retell in writing the advertising text of grade VIIIIth C students of Junior High School of Negeri 6 Tabanan in the 2022/2023 academic year after applying the discovery learning method had increased. This is evidenced by the average score obtained in the pre-cycle of 68.12%. In the first cycle, the average value of students increased to 74.06%. In the second cycle the average student score was 80.00%. The increase from the pre-cycle to the first cycle was 8.71%. The increase from the first cycle to the second cycle was 8.01%. The increase in value is a sign that the ability to retell in writing the advertising text of students in grade VIIIth C Junior High School of Negeri 6 Tabanan in the 2022/2023 academic year is getting better because it always increases.